Kemampuan Menggunakan Mikroskop Siswa Kelas Vii Smp Negeri 1 Sidoharjo Wonogiri Semester Genap Tahun Ajaran 2015/2016 - MUSTIKA SARASWATI, PUTRI, Drs. Djumadi, M.Kes (2016)
Microscope (Greek: micros = small and scopein = view) was a tool to see objects that were too small to see with the eyes of the rough. The purpose of this study was to determine the ability to used a microscope class VII SMP Negeri 1 Sidoharjo Wonogiri second semester of the 2015/2016 academic year. This type of research was descriptive qualitative. The strategy in this study used case studies that emphasize depth of understanding of the issues examined. The instrument used was the performance assessment with an assessment rubric scale, interviews, and documentation. Data analysis technique used was descriptive qualitative. Based on the results showed that the ability to used a microscope class VII SMP Negeri 1 Sidoharjo Wonogiri second semester of the 2015/2016 academic year by how to bring microscopes (100%), preparing microscopes for observation (93.38%), making preparations (62.3%), preparing object glass and cover glass (62.5%), preparing preparations (97.79%), get a focus on weak magnification (72.55%), get a focus on strong magnification (64.21%), draw results observations (61.75%), after the treatment was completed observations (93.62%) and safety (97.05%). Thus, it can be concluded that the ability to used a microscope class VII SMP Negeri 1 Sidoharjo Wonogiri second semester of the 2015/2016 academic year (80.51%). Average highs in the ability to used a microscope aspects of bringing a microscope (100%), while the lowest average in the aspects of drawing the observations (61,75%).